تحولات الرابط الاجتماعي في المجتمع الجزائري - قريد, سمير (جامعة الوادي - University of Eloued, 2022)
نسعى من خلال هذا المقال إلى تتبع مراحل تطور الرابط الاجتماعي في المجتمع الجزائري بدءا بمرحلة ما قبل الاستعمار، وذلك بهدف تقديم صورة عامة عن خصائص الرابط الاجتماعي خلال هذه الفترة، مرورا بمرحلة الاستعمار الفرنسي التي غرفت تفكيكا ممنهجا للرابط الاجتماعي، ثم مرحلة الثورة التحريرية التي عملت على تكوين أشكالا خاصة من التضامن القائم على الأخوة كشكل من أشكال الرابط الاجتماعي من أجل تحقيق غاية مشتركة هي التحرر الوطني، وصولا إلى مرحلة الاستقلال التي عرفت تحولات اجتماعية واقتصادية وسياسية كان لها الأثر السلبي على بنية الرابط الاجتماعي. Through this article, we seek to trace the stages of the transformation of the social tie in Algerian society, starting with the pre-colonial stage, with the aim of providing a general clarification of the characteristics of the social tie during that period, passing through the stage of French colonialism, which witnessed a process of deliberate dismantling of the social bond, and then the stage of the liberation revolution that It sought to form special forms of solidarity based on brotherhood as a form of social tie, in order to achieve a common goal, which is national liberation, up to the stage of independence, which witnessed social, economic and political transformations, which had a negative impact on the structure of the social tie.
مقاربة سوسيوتاريخية
مقال
Keywords: تحولات/ الرابط الاجتماعي/ المجتمع الجزائري/ مقاربة سوسيوتاريخية; Transformations / The Social tie Algerian society /a sociohistorical Approach